ENGLISH VERS LIBRE PROSODY (AUDITORY ANALYSIS RESULTS) - Olga Morgunova; Tetiana Shkurko; Olena Pavlenko (National Technical University of Ukraine "Kyiv Polytechnic Institute", 2019)
The paper focuses on the vers libre prosody taking into account the auditory aspect of its oral actualisation. The main hypothesis of the study is that vers libre is constituted with a range of definite stable prosodic features that allow referring it to versification and at the same time to something different from a metered text and prose. Stimuli include written and oral presentations of vers libre. Some prosaic extracts have been analysed to compare them with vers libre. In addition, vers libre has been written as a piece of prose (pseudo-prose) and recited orally by native speakers having RP pronunciation. The prose has been written as vers libre, i.e. divided into lines (pseudo-verse), and cited as a verse. It helps identify the role of prosodic features in constituting vers libre specificity. The authors come to the conclusion that vers libre is correlated with a rather comprehensive set of prosodic features that determine its specificity. The quality of the "poetic speech" is formed by all components of its prosodic structure. The most important poetic features of vers libre are presented by its accent system and rhythmical structure. The accentual features include decentralisation of an accent in free verse lines; the rhythmic dominant on the last ictus in the line; an additional emphasis in polysyllabic words. The typical rhythmic structures in the vers libre are monosyllabic 1/1, disyllabic 2/2, 2/1, three-syllabic 3/2, 3/3 and four-syllablic 4/3 ones. The difference between vers libre and prose is demonstrated mainly by temporal and pausal features.